Community Structure, Abundance and Potential Functions of Bacteria and Archaea in the Sansha Yongle Blue Hole, Xisha, South China Sea - He, Hui; Fu, Lulu; Liu, Qian; Fu, Liang; Bi, Naishuang; Yang, Zuosheng; Zhen, Yu (Frontiers in Microbiology, 2019)
The Sansha Yongle Blue Hole is the deepest blue hole in the world and exhibits unique environmental characteristics. In this paper, Illumina sequencing and qPCR analysis were conducted to obtain the microbial information in this special ecosystem. The results showed that the richness and diversity of bacterial communities in the hole was greater than those of archaeal communities, and bacterial and archaeal communities were dominated by Proteobacteria and Euryarchaeota, respectively. Temperature and nitrate concentration significantly contributed to the heterogeneous distribution of major bacterial clades; salinity explained most variations of the archaeal communities, but not significant. A sudden increase of bacterial 16S rRNA, archaeal 16S rRNA, ANAMMOX 16S rRNA, nirS and dsrB gene was noticed from 90 m to 100 m in the hole probably due to more phytoplankton at this depth. Sulfur oxidation and nitrate reduction were the most abundant predicted ecological functions in the hole, while lots of archaea were predicted to be involved in aerobic ammonia oxidation and methanogenesis. The co-occurrence network analysis illustrated that a synergistic effect between sulfate reduction and sulfur oxidation, and between nitrogen fixation and denitrification, a certain degree of coupling between sulfur and nitrogen cycle was also observed in the hole. The comparisons of bacterial and archaeal communities between the hole and other caves in the world (or other areas of the South China Sea) suggest that similar conditions are hypothesized to give rise to similar microbial communities, and environmental conditions may contribute significantly to the bacterial and archaeal communities.